Perancangan Sistem Forecasting di Perusahaan Kayu UD. 3G dengan Metode ARIMA - Peter Sutanto; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
UD. 3G is a private company that specialize in selling processed wood. UD. 3G still not have a forecasting system so as to procure stock still using manually estimate by looking at the previous sale. So it makes UD. 3G experience many losses because a lot of unsold wood stock becomes broken due the various factors. Therefore, requires the forecasting system that is easy to use and helps estimate items that must be purchased. The process for making this forecasting is through several steps, the first step is do a survey and needs analysis. The second step is taking sales data in 2013, 2014 and 2015. And the third step is making a flowchart and entity relation diagram design, then perform database creation. The process of developing program is using PHP programming language, MySQL for database and for the forecasting calculation is using ARIMA method. Based on the result obtained from the testing, system can store inventory data, do forecasting calculation based on the sales data, displaying graphs of the result of forecasting, have a shortcut key to print forecasting report and do error calculation to get the smallest error from three methods so can be used to perform the best forecasting.